2016
DOI: 10.1155/2016/4197693
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Training on Three-Dimensional versus Two-Dimensional Laparoscopic Systems on Acquisition of Laparoscopic Skills in Novices: A Prospective Comparative Pilot Study

Abstract: In this prospective educational study, 10 medical students (novices) were randomized to practice two basic laparoscopic tasks from the MISTELS program, namely, Pegboard Transfer (PT) and Intracorporeal Knot Tying (IKT) tasks, using either a 2D or a 3D laparoscopic platform. There was no significant difference between both groups in the baseline assessments (PT task: 130.8 ± 18.7 versus 151.5 ± 33.4; p = 0.35) (IKT task: 123.9 ± 41.0 versus 122.9 ± 44.9; p = 0.986). Following two training sessions, there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Similar findings have been described in medical training studies exploring options for efficiently training novices with laparoscopic skills. One study observed the impact of training in two-dimensional versus three-dimensional laparoscopic systems and found that the results were comparable between the two systems even though the threedimensional laparoscopic system was predicted to be more effective (Noureldin et al 2016). This demonstrates that, while training in a VR environment can be effective in improving spatial cognitive abilities, the complexity of acquiring the materials and costs may not be worth the effort.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been described in medical training studies exploring options for efficiently training novices with laparoscopic skills. One study observed the impact of training in two-dimensional versus three-dimensional laparoscopic systems and found that the results were comparable between the two systems even though the threedimensional laparoscopic system was predicted to be more effective (Noureldin et al 2016). This demonstrates that, while training in a VR environment can be effective in improving spatial cognitive abilities, the complexity of acquiring the materials and costs may not be worth the effort.…”
Section: Discussionmentioning
confidence: 99%